Effect of Robot-Assisted Gait Training on Selective Voluntary Motor Control in Ambulatory Children with Cerebral Palsy - Zarkovic, Dragana; Sorfova, Monika; Tufano, James J; Kutilek, Patrik; Viteckova, Slavka; Groleger-Srsen, Katja; Ravnik, David (Indian pediatrics, 2020)
This pilot study investigated the efficacy of a four week robot-assisted gait training in twelve children with spastic diparesis. Short-term results and a 3-month follow-up showed statistically significantly increased selective motor control, walking farther distances, gross motor score, and decreased joint contractures.
Keywords: Robotics; terapie cvičením; Humans; Child; lidé; mozková obrna; Cerebral Palsy; dítě; Pilot Projects; Exercise Therapy; chůze (způsob); pilotní projekty; Gait; robotika